Aggregated applications and benefits of energy storage systems with application-specific control methods: A review. (August 2017) - Katsanevakis, Markos; Stewart, Rodney A.; Lu, Junwei
Abstract: Distributed energy storage systems (ESSs) are becoming essential components for the operation of the increasingly complex electricity grid, where dispersed generation is causing power-flows occurring both top-down and bottom-up. Specifically, the combination of ESSs coupled with application-specific control methods can achieve the interdependent objectives of system stakeholders such as the system operator, electrical utilities, retailers, equipment vendors, the government and the electricity customers. The necessity for an accelerated rate of transition to a multi-directional grid arrangement has been exacerbated by the rapid proliferation of distributed renewable energy sources (RESs) that are now price comparable to traditional supply sources. While there are review articles covering ESS technologies and applications as well as the plethora of future advanced grid arrangements that may eventuate, there is none which comprehensively covers individual and aggregated ESS applications and the corresponding benefits, comparing different technology selection methods and providing application-specific controls. Both operational and monetary benefits are identified and critically reviewed from the perspective of the aforementioned stakeholders. Wholesale and retail energy market regimes are also considered for monetisation of the benefits. The control methods that are provided cover both balanced and unbalanced grid conditions. This comprehensive review paper will be of immense value to researchers and practitioners seeking to understand and unpack the aggregated benefits of ESS in the electricity grid.